Non-neuronal cells in amyotrophic lateral sclerosis — from pathogenesis to biomarkers - Vahsen, BF; Gray, E; Thompson, AG; Ansorge, O; Anthony, DC; Cowley, SA; Talbot, K; Turner, MR (Springer Nature, 2021)
The prevailing motor neuron-centric view of amyotrophic lateral sclerosis (ALS) pathogenesis could be an important factor in the failure to identify disease-modifying therapy for this neurodegenerative disorder. Non-neuronal cells have crucial homeostatic functions within the CNS and evidence of involvement of these cells in the pathophysiology of several neurodegenerative disorders, including ALS, is accumulating. Microglia and astrocytes, in crosstalk with peripheral immune cells, can exert both neuroprotective and adverse effects, resulting in a highly nuanced range of neuronal and non-neuronal cell interactions. This Review provides an overview of the diverse roles of non-neuronal cells in relation to the pathogenesis of ALS and the emerging potential of non-neuronal cell biomarkers to advance therapeutic development.